2005
DOI: 10.1002/bjs.4935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supervised surgical training on outcomes after resection of colorectal cancer

Abstract: Outcomes after resection for colorectal cancer did not differ between the consultant and trainees in the context of a closely supervised training programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 14 publications
3
44
0
2
Order By: Relevance
“…We believe it is more appropriate and representative to give the sample size for each variable on which analysis was performed by providing the number of cases in the overall total number of hips reviewed (1089) that had data for a particular variable. The study also included all operations performed by a mixture of consultant-level surgeons and trainee surgeons, which may have affected clinical outcomes, although a couple studies have shown no such differences [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…We believe it is more appropriate and representative to give the sample size for each variable on which analysis was performed by providing the number of cases in the overall total number of hips reviewed (1089) that had data for a particular variable. The study also included all operations performed by a mixture of consultant-level surgeons and trainee surgeons, which may have affected clinical outcomes, although a couple studies have shown no such differences [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…All operations included in this study were carried out by a single consultant surgeon (NDM) or by a suitably qualified trainee of at least specialist registrar grade (years [4][5][6] under the direct supervision and guidance of NDM who was scrubbed in theatre during the operations. The first surgeon in this study was defined as the first surgeon recorded in the notes; if the majority of the procedure, including the anastomosis, was performed by a trainee, it was recorded as a trainee procedure.…”
Section: Methodsmentioning
confidence: 99%
“…This should not, however, be at the expense of patient care and operative outcome. A number of other studies have looked at outcomes of procedures performed by consultants versus trainees in vascular [1][2][3][4] and lower gastrointestinal surgery, [5][6][7] but few papers have done the same in upper gastrointestinal surgery, 8 with none looking at survival and recurrence of malignancy. This paper analyses the outcomes of oesophagectomies performed by a consultant surgeon compared with those performed by trainees (SpRs years 4-6) operating under direct supervision.…”
mentioning
confidence: 99%
“…Les impacts fonctionnels ont été mesurés dans six des 14 articles médicaux retenus, dont six ont traité de la mortalité dans un contexte chirurgical [16][17][18][19][20] la satisfaction des patients [3] . Dans notre revue systématique, la mortalité a d'emblée été classifiée parmi les impacts fonctionnels comme un indicateur de l'état de santé associé au but visé par l'intervention.…”
Section: Impacts Fonctionnelsunclassified
“…Dans tous les cas, aucune différence n'est notée quant au taux de ré-excision intra-opéra-tive et de ré-opération chez les patientes qui ont subi une chirurgie du sein [20] , aux effets indésirables majeurs et aux indicateurs secondaires (durée du séjour à l'hôpital et à l'unité des soins intensifs, taille et type de valvule) chez des patients avec remplacement valvulaire aortique [14] , au retour en salle d'opé-ration et aux autres complications chez des patients opérés par laparoscopie [15] , aux complications postopératoires de patients opérés pour un pontage aorto-coronarien [16] , aux retours non planifiés au service d'urgence et à la fréquence des admissions à l'hôpital [19] ou quant à la douleur ressentie par des patients lors d'une cystoscopie diagnostique [28] .…”
Section: Impact Sur Les Processusunclassified